Phylogeny of the family Characidae (Teleostei: Characiformes): from characters to taxonomy - Mirande, Juan Marcos (2010)
The family Characidae is the most diverse among Neotropical fishes. Systematics of this family are mainly based on pre cladistic papers, and only recently a phylogenetic hypothesis for Characidae was proposed by the author. That phylogeny was based on 360 morphological characters studied for 160 species, including representatives of families related to Characidae. This paper is based on that phylogenetic analysis, with the analyzed characters described herein and documented, accompanied by comparisons of their definition and coding in previous papers. Synapomorphies of each node of the proposed phylogeny are listed, comparisons with previous classifications provided, and autapomorphies of the analyzed species listed. Taxonomic implications of the proposed classification and the position of the incertae sedis genera within Characidae are discussed. A discussion of the phylogenetic information of the characters used in the classical systematics of the Characidae is provided.